the Relationship between Knowledge about Meningitis Vaccination and Timeliness of Vaccination in Umrah Pilgrims at BKK Class I Samarinda - Nozomi, Alwan Zakki; Wisnuwardani, Ratih Wirapuspita; Pakki, Irfansyah Baharudin (PT.Mantaya Idea Batara, 2025)
Meningitis is a global health problem that poses a high risk to Umrah pilgrims. WHO designated Saudi Arabia as a country that has a high incidence of meningitis (meningitis belt). Data from the Ministry of Health in 2024 is estimated at 10,658 cases of meningitis. Meningitis vaccination is a vaccination to protect against meningitis. The vaccine is given at least 14 days before departure to maximize immunity. Knowledge about vaccination is one of the factors that influence a person to vaccinate in a timely manner. This study aims to determine how the relationship between knowledge about meningitis vaccination and the timeliness of vaccination in umrah pilgrims at BKK class I samarinda. Data collection using questionnaires on 166 respondents with the Chi-Square test. Of the 166 respondents, 98 respondents (59.04%) had a good level of knowledge and vaccinated on time, 7 respondents (4.24%) had a good level of knowledge and did not vaccinate on time, 13 respondents (7.83%) had a sufficient level of knowledge and vaccinated on time, 41 respondents (24.7%) had a sufficient level of knowledge and did not vaccinate on time, 1 respondent (0.6%) had a poor level of knowledge and vaccinated on time, 6 respondents (3.61%) had a poor level of knowledge and did not vaccinate on time. The results of the chi-Square statistical test showed that there was a significant relationship between the level of knowledge about meningitis vaccination and the timeliness of vaccination (p=0.00001).